2021
DOI: 10.3389/fmicb.2021.700637
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Dominant Freshwater Bacterioplankton Lineages Using a High-Throughput Dilution-to-Extinction Culturing Approach Over a 1-Year Period

Abstract: Although many culture-independent molecular analyses have elucidated a great diversity of freshwater bacterioplankton, the ecophysiological characteristics of several abundant freshwater bacterial groups are largely unknown due to the scarcity of cultured representatives. Therefore, a high-throughput dilution-to-extinction culturing (HTC) approach was implemented herein to enable the culture of these bacterioplankton lineages using water samples collected at various seasons and depths from Lake Soyang, an olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Nanopelagicales’, Acidimicrobiia (also known as acIV; Newton et al, 2011) are commonly found in freshwater systems, albeit in lower numbers (Figure 8A). Although several strains have been isolated (Henson et al, 2020; Kim, Islam, et al, 2021), no genomes of cultures have so far been published, thus MAGs are the only source of genomic information for the acIV lineage. The families Ilumatobacteraceae, ‘ Ca .…”
Section: Commonly Found Freshwater Microbes: the Freshwater Pelagial ...mentioning
confidence: 99%
“…Nanopelagicales’, Acidimicrobiia (also known as acIV; Newton et al, 2011) are commonly found in freshwater systems, albeit in lower numbers (Figure 8A). Although several strains have been isolated (Henson et al, 2020; Kim, Islam, et al, 2021), no genomes of cultures have so far been published, thus MAGs are the only source of genomic information for the acIV lineage. The families Ilumatobacteraceae, ‘ Ca .…”
Section: Commonly Found Freshwater Microbes: the Freshwater Pelagial ...mentioning
confidence: 99%
“…The concentration of nitrate does not differ between the hypolimnion and the epilimnion layer in any season. Ammonium is only detectable in the lake hypolimnion during spring [ 61 ]. The lake hypolimnion is an extremely low-nutrient environment, and the nutrient levels decrease gradually over time from spring to winter.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only two species ( Polynucleobacter rarus and Polynucleobacter kasalickyi ) have been described ( 3 , 4 ). Isolation and cultivation of PnecA bacteria have rarely been successful ( 3 6 ). Thus, the genomic information on PnecA bacteria is very limited.…”
Section: Announcementmentioning
confidence: 99%